Objective and subjective acoustical parameters in catholic churches - António P. O.Carvalho (1997)
This study reports on subjective and objective acoustical field measurements made in a survey of 36 Catholic churches in Portugal built in the last 14 centuries. Monaural acoustical measurements (C80,D50,EDT, L, RT and TS) were taken at several source/receiver locations in each church and a group of college students was asked to judge the subjective quality of music. The listeners in each church evaluated live music performances at similar locations in each room. Evaluation sheets were used to record the listeners overall impressions of room acoustics qualities and also Loudkess, Reverberance, Intimacy, Envelopment, Directionality, Balance, Clarity, Echoes, and Background Noise. This paper concentrates on the relationships of the subjective parameters with the objective room acoustics measures and with the architectural features of the churches.